2020 European Control Conference (ECC) 2020
DOI: 10.23919/ecc51009.2020.9143773
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of spatially distributed intensive biological systems

Abstract: We introduce a new type of bioreactor model that offers a representation of the spatial features of a pilot scale upflow fixed bed reactor. This model couples fluid dynamics and biological activity in order to obtain the internal gradient of substrate and biomass concentrations. We take advantage of reactor geometry to reduce the model to a single spatial dimension in the section containing the fixed bed but in other sections, we consider a 3D model with Navier-Stokes equations for the fluid dynamics. To repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…It has been shown, for some time now, that relatively simple models can reproduce complex real world systems, albeit with a limited domain of validity (Haddon et al, 2020;Pérémé et al, 2023;Haddon et al, 2023). Similarly, we have found that it is also possible to replicate a simulation of a detailed complex model with a simplified model.…”
Section: Double Modeling Methodssupporting
confidence: 65%
“…It has been shown, for some time now, that relatively simple models can reproduce complex real world systems, albeit with a limited domain of validity (Haddon et al, 2020;Pérémé et al, 2023;Haddon et al, 2023). Similarly, we have found that it is also possible to replicate a simulation of a detailed complex model with a simplified model.…”
Section: Double Modeling Methodssupporting
confidence: 65%